Mechanochemical synthesis of CeB6 nanopowder - Ha, Taejun; Lee, Young-Su; Lee, Joonho; Shim, Jae-Hyeok (ELSEVIER SCI LTD, 2019)
Mechanochemical synthesis of CeB6 nanopowder was performed using a mixture of CeCl3, CeO2, B2O3 and either Mg or MgH2. The reaction for the CeO2-3B(2)O(3)-11MgH(2) mixture to form CeB6 and MgO gradually proceeds during ball milling, while the mechanically induced self-propagating reaction (MSR) behavior is observed during ball milling of the CeO2-3B(2)O(3)-11 Mg mixture. X-ray diffraction patterns of the CeO2-3B(2)O(3)-11MgH(2) mixture indicate that CeH2+x exists as an intermediate phase during the reaction. Scanning electron microscopy indicates that the particle size of CeB6 powder from the CeO2-3B(2)O(3)-11MgH(2) mixture is much smaller than that from the CeO2-3B(2)O(3)-11 Mg mixture. Transmission electron microscopy revealed that CeB6 particles 10-30 nm in size from the CeO2-3B(2)O(3)-11MgH(2) mixture are highly agglomerated with surface oxide layers. The mechanochemical reaction of the 2CeCl(3)-6B(2)O(3)-21MgH(2) mixture produces CeB6 instead of Ce(BH4)(3).
Keywords: CERIUM HEXABORIDE; TEMPERATURE; NABH4